An Empirical Study of Requirements Elaboration - Malik, Ali Afzal; Boehm, Barry (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2008: Anais do XXII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2008.21327, 2008)
This paper describes an empirical study undertaken to investigate the quantitative aspects of the phenomenon of requirements elaboration which deals with the transformation of high-level goals into low-level requirements. Prior knowledge of the magnitude of requirements elaboration is instrumental in developing early estimates of a project’s cost and schedule. This study examines the data on capability goals and capability requirements of 20 real-client, MS-student, team projects done at USC. Metrics for data collection and analysis are described along with the utility of the results they produce. These results suggest some relationship between the nature of projects and the size of requirements elaboration.